Metode Hilah (Dalih Hukum) Dalam Fikih Muamalah Kontemporer - Muhamad Takhim (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2019)
Abstract The development of halal products and their legal status cannot be separated from the method of fiqh proposal. One of the things that became controversy and differences of opinion among scholars was hilah. In its development, this method apparently still exists and is used by the Ulama to conclude the stipulation in Shari'a law (istimbat). In the case, for example, the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), although not explicitly expressing it explicitly, was found to have used this concept. Hilah is part of the ulama ijtihad product as mentioned above, as a way out in solving contemporary muamalah fiqh problems. Is the theory still relevant and needed in solving contemporary legal cases or is it considered a deviation of law. The author in this study uses a descriptive analysis approach, describing the opinions of the ulama 'along with their arguments and then analyzing it, so the writer has the conclusion that the hilah method is still needed and relevant as a solution in solving contemporary muamalah problems and not constituting a legal deviation. Keywords: Hilah, Hujjah, Istimbat